Battery cell of solid-state battery, preparation method of battery cell of solid-state battery and solid-state battery

By coating the composite protective film on the positive pole sheet and negative pole tablets of the solid battery cell, the problem of poor interface stability and poor contact in the solid battery in the solid battery is solved, and the battery performance is optimized and the energy density is improved.

CN119361850APending Publication Date: 2025-01-24GUANGDONG LIWANG NEW ENERGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411560736.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

In the existing solid-state battery preparation process, the interface stability and contact between the solid-state electrolyte and the electrode material are poor, resulting in limited battery performance optimization and difficult to take into account light weight, high energy density and safety performance.

Method used

In the battery cells of the solid battery, the surface of the positive poles and the negative pole sheets form a composite protective film through coating, including MOF materials, solid electrolyte materials, adhesives and lithium salt to reduce the solid electrolyte coating of the diaphragm Demand, thereby using thinner diaphragms to optimize the overall performance of the battery.

Benefits of technology

By using a composite protective film, the contact area and stability of solid electrolytes and electrode materials are improved, the dynamic performance and high temperature resistance of the battery are optimized, the weight of the battery is reduced, the energy density is improved, and the process is difficult.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361850A_ABST
    Figure CN119361850A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of battery materials, and discloses a battery cell of a solid-state battery, a preparation method of the battery cell of the solid-state battery and the solid-state battery. Composite protective films comprising an MOF material, a solid-state electrolyte material, an adhesive and lithium salt are formed on the surfaces of a positive pole piece and a negative pole piece through coating respectively; according to the present invention, the solid electrolyte material does not need to be coated on the separator, such that the thin separator with the thickness of less than 10 [mu] m can be used so as to easily reduce the weight and improve the energy density, the process difficulty can be reduced, and the dynamic performance and the high temperature resistance of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a solid-state battery cell, a method for preparing the solid-state battery cell, and a solid-state battery. Background Art

[0002] Solid-state battery technology, as a key development leading the development of the battery field, has the core advantage of using solid electrolytes to replace traditional liquid electrolytes. This innovative measure has significantly improved the safety performance and energy density of batteries, thus becoming an important trend in the evolution of battery technology.

[0003] However, it is worth noting that the interfacial stability and contact between the solid electrolyte and the electrode material constitute the core challenge that restricts the performance optimization of solid-state batteries. At present, the solid-state battery preparation process at the industrial level generally follows a strategy: that is, the solid electrolyte material is coated on the polymer battery separator, and then assembled into a semi-(or quasi-) solid-state battery, or a solid-state battery cell. Although this process reduces the dependence on liquid components to a certain extent, even if there is only a small amount of liquid, it will still cause a large interface impedance problem between the positive and negative electrodes and the separator, thereby affecting the overall performance of the battery.

[0004] In addition, the diaphragms widely used in the prior art usually have a thickness between 10um and 16um. The selection of this size range is neither random nor optimal: on the one hand, although a diaphragm that is too thin is conducive to reducing weight and improving energy density, it may reduce overall safety performance and increase the technical difficulty of solid electrolyte coating; on the other hand, if the diaphragm is too thick, although it can enhance structural stability to a certain extent, it will undoubtedly push up production costs and sacrifice the overall energy density of lithium-ion batteries due to the increase in material volume. What is more serious is that under high-temperature working conditions, the positive and negative electrode materials inside the battery are prone to falling off, the so-called "powder shedding" phenomenon, which further threatens the stable operation of the battery.

[0005] In view of the above challenges, improving and upgrading the existing solid-state battery preparation technology has become a key issue that needs to be addressed urgently.

[0006] The above information is presented as background information only to assist with understanding the present disclosure and no determination or admission is made as to whether any of the above may be used as prior art with respect to the present disclosure. Summary of the invention

[0007] The present invention provides a solid-state battery cell, a method for preparing the solid-state battery cell and a solid-state battery, so as to solve the problems existing in the prior art.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] In a first aspect, the present invention provides a solid-state battery cell, comprising a positive electrode sheet, a negative electrode sheet, a separator and a composite protective film; wherein:

[0010] The positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence;

[0011] The positive electrode sheet and the negative electrode sheet each include a first surface and a second surface that are arranged opposite to each other, wherein the first surface is a surface close to one side of the diaphragm;

[0012] The composite protective film is formed on both the first surface and the second surface by coating;

[0013] The composite protective film comprises MOF material, solid electrolyte material, adhesive and lithium salt.

[0014] Furthermore, in the battery cell of the solid-state battery, the MOF material is UIO-66 or ZIF-8;

[0015] The MOF material is prepared by a template method or a direct synthesis method.

[0016] Furthermore, in the battery cell of the solid-state battery, the solid electrolyte material is any one or a combination of PEO, PAN, LATP, and LLZO.

[0017] Furthermore, in the battery cell of the solid-state battery, the lithium salt is any one or a combination of LiTFSI, LiFSI, and LiCF3SO3.

[0018] Furthermore, in the battery cell of the solid-state battery, the thickness of the composite protective film is 2 um.

[0019] Furthermore, in the battery cell of the solid-state battery, the thickness of the diaphragm is less than 10 um.

[0020] In a second aspect, the present invention provides a method for preparing a solid-state battery cell, which is used to prepare the solid-state battery cell provided in the first aspect, and the method comprises:

[0021] The MOF material, the solid electrolyte material and the binder are mixed and dissolved in a certain proportion, and lithium salt is added thereto to obtain a mixed slurry;

[0022] The mixed slurry is uniformly coated on two opposite surfaces of the positive electrode sheet and the negative electrode sheet respectively by coating technology;

[0023] Drying and curing the coated positive electrode sheet and negative electrode sheet, and rolling them to form composite protective films on the surfaces of the positive electrode sheet and negative electrode sheet respectively;

[0024] The positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence to form a solid-state battery cell.

[0025] Furthermore, in the preparation method, the step of mixing and dissolving the MOF material, the solid electrolyte material and the binder in a certain proportion, and adding lithium salt thereto to obtain the mixed material comprises:

[0026] Mix and dissolve the MOF material, solid electrolyte material and binder in a certain proportion, and add lithium salt thereto;

[0027] The mixture was stirred at room temperature for 24 hours to obtain a mixed slurry.

[0028] Furthermore, in the preparation method, the method further comprises:

[0029] The NCM material, conductive acetylene black and adhesive are mixed in a mass ratio of 8:1:1, dispersed in NMP, coated on two opposite surfaces of the aluminum foil, and dried to obtain the positive electrode sheet.

[0030] In a third aspect, the present invention provides a solid-state battery, comprising a battery cell of the solid-state battery provided in the first aspect above.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The present invention provides a solid-state battery cell, a method for preparing a solid-state battery cell, and a solid-state battery. A composite protective film including MOF material, solid-state electrolyte material, adhesive, and lithium salt is formed by coating the surfaces of a positive electrode plate and a negative electrode plate, respectively, so that there is no need to coat the solid-state electrolyte material on the diaphragm. Therefore, not only a thinner diaphragm of less than 10 um can be used, which is beneficial to reducing weight and improving energy density, but also the process difficulty can be reduced and the dynamic performance and high temperature resistance of the battery can be improved.

[0033] The present invention has other features and advantages, which will be apparent from or will be described in detail in the accompanying drawings and the following detailed description incorporated herein, which together serve to explain the specific principles of the invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0035] Figure 1 is a schematic structural diagram of a solid-state battery cell provided in Embodiment 1 of the present invention;

[0036] Figure 2 It is a schematic flow chart of a method for preparing a solid-state battery cell provided in the second embodiment of the present invention;

[0037] Figure 3 This is a diagram showing the powder removal state of the diaphragm surface of different groups of battery cells mentioned in Example 2 of the present invention after being subjected to high-temperature treatment at 85°C.

[0038] Reference numerals:

[0039] Positive electrode sheet 1, negative electrode sheet 2, separator 3, composite protective film 4. DETAILED DESCRIPTION

[0040] In order to explain in detail the possible application scenarios, technical principles, specific schemes that can be implemented, and the purposes and effects that can be achieved, the following is a detailed description of the specific embodiments listed in conjunction with the accompanying drawings. The embodiments described herein are only used to more clearly illustrate the technical solutions of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0041] Reference to "embodiment" herein means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The term "embodiment" appearing in various places in the specification does not necessarily refer to the same embodiment, nor does it particularly limit its independence or association with other embodiments. In principle, in the present application, as long as there is no technical contradiction or conflict, the various technical features mentioned in the embodiments can be combined in any way to form a corresponding implementable technical solution.

[0042] Unless otherwise defined, the technical terms used in this document have the same meanings as those generally understood by those skilled in the art to which this application belongs; the use of relevant terms in this document is only for describing specific embodiments and is not intended to limit this application.

[0043] In the description of this application, the term "and / or" is an expression used to describe the logical relationship between objects, indicating that three relationships may exist, for example, A and / or B, which means: A exists, B exists, and A and B exist at the same time. In addition, the character " / " in this article generally indicates that the objects before and after are in an "or" logical relationship.

[0044] In the present application, terms such as “first” and “second” are merely used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship of quantity, priority or sequence between these entities or operations.

[0045] Without further limitations, in this application, the words "include", "comprises", "has" or other similar expressions used in the sentences are intended to cover non-exclusive inclusion. These expressions do not exclude the presence of additional elements in the process, method or product including the elements, so that the process, method or product including a series of elements may include not only those limited elements, but also other elements not explicitly listed, or also include elements inherent to such process, method or product.

[0046] In this application, expressions such as "greater than", "less than", "exceed" and the like are understood to exclude the number itself; expressions such as "above", "below", "within" and the like are understood to include the number itself. In addition, in the description of the embodiments of this application, "multiple" means more than two (including two), and similar expressions related to "multiple" are also understood in this way, such as "multiple groups", "multiple times", etc., unless otherwise clearly and specifically limited.

[0047] In the description of the embodiments of the present application, space-related expressions used, such as "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "vertical", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc., indicate the orientation or position relationship based on the orientation or position relationship shown in the specific embodiments or drawings, and are only for the convenience of describing the specific embodiments of the present application or facilitating the reader's understanding, and do not indicate or imply that the referred device or component must have a specific position, a specific orientation, or be constructed or operated in a specific orientation, and therefore cannot be understood as a limitation on the embodiments of the present application.

[0048] Unless otherwise expressly specified or limited, in the description of the embodiments of the present application, the terms such as "install", "connect", "connect", "fix", "set", etc. used should be understood in a broad sense. For example, the "connection" can be a fixed connection, a detachable connection, or an integrated setting; it can be a mechanical connection, an electrical connection, or a communication connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium; it can be the internal connection of two elements or the interaction relationship between two elements. For technicians in the technical field to which the present application belongs, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.

[0049] Embodiment 1

[0050] In view of the defects of the above-mentioned prior art, the applicant, based on many years of rich practical experience and professional knowledge in the design and manufacture of such products, and in conjunction with the application of academic theory, actively conducts research and innovation in the hope of creating a technology that can solve the defects of the prior art. After continuous research and design, and after repeated trial samples and improvements, the present invention with real practical value was finally created.

[0051] Please refer to Figure 1 The embodiment of the present invention provides a solid-state battery cell, comprising a positive electrode sheet 1, a negative electrode sheet 2, a separator 3 and a composite protective film 4; wherein,

[0052] The positive electrode sheet 1, the separator 3 and the negative electrode sheet 2 are stacked in sequence;

[0053] The positive electrode sheet 1 and the negative electrode sheet 2 each include a first surface and a second surface that are arranged opposite to each other, wherein the first surface is a surface close to one side of the diaphragm 3;

[0054] The composite protective film 4 is formed on both the first surface and the second surface by coating;

[0055] The composite protective film 4 includes MOF material, solid electrolyte material, adhesive and lithium salt.

[0056] It should be noted that in the embodiment of the present invention, the solid electrolyte material is no longer coated on the diaphragm, but a composite protective film including MOF (metal organic framework) material, solid electrolyte material, adhesive and lithium salt is formed on the surface of the positive electrode sheet 1 and the negative electrode sheet 2 by coating, so that a stable solid electrolyte-electrode interface can be formed on the surface of the positive electrode sheet 1 and the negative electrode sheet 2, which can not only improve the contact area and stability between the solid electrolyte and the electrode material and the diaphragm, and optimize the overall performance of the battery cell of the solid-state battery, but also because a thinner diaphragm with a thickness of less than 10um can be used, thereby reducing the overall weight of the battery, significantly improving the energy density, and greatly simplifying the production process, reducing the difficulty of technical implementation. In addition, the design further optimizes the dynamic characteristics of the battery, significantly improves its high temperature resistance, and opens up a new path for the development of solid-state batteries.

[0057] In one implementation of this embodiment, the MOF material having high ionic conductivity and good mechanical properties is selected to ensure that the performance of the composite protective film 4 is optimal, such as UIO-66, ZIF-8, etc.;

[0058] When preparing these MOF materials, two methods can be selected: template method or direct synthesis method. Template method is a method that guides the growth of MOF materials through a preset template structure. It can accurately control the morphology and pore structure of MOF, thereby optimizing its ion conduction path and mechanical support capacity. Direct synthesis is a more direct method that does not require additional templates, but directly generates MOF materials through self-assembly of metal ions and organic ligands in the reaction system. Both methods can effectively prepare MOF materials that meet the requirements, providing a solid foundation for the subsequent coating of composite protective films.

[0059] In one implementation of this embodiment, the selection of solid electrolyte materials has been carefully considered to ensure comprehensive optimization of the performance of the battery cell. This embodiment selects a series of high-performance materials, including polyethylene oxide (PEO), polyacrylonitrile (PAN), lithium aluminum titanium phosphate (LATP) and lanthanum zirconium oxide (LLZO), which can be used alone or in combination in any proportion to form a solid electrolyte layer in the composite protective film 4.

[0060] Polyethylene oxide (PEO) and polyacrylonitrile (PAN) are polymer solid electrolytes with good flexibility and film-forming properties, which can ensure close contact between the electrolyte layer and the electrode material while providing a stable ion conduction channel. Lithium aluminum titanium phosphate (LATP) and lanthanum zirconium oxide (LLZO) are inorganic solid electrolytes, which are known for their high ionic conductivity and excellent thermal stability, and can effectively improve the safety performance and high temperature resistance of the battery cell.

[0061] By carefully selecting and combining these solid electrolyte materials, the composite protective membrane 4 can be fully optimized in terms of ion conduction, mechanical strength, thermal stability, and electrode compatibility, thereby further improving the overall performance of the solid-state battery cell.

[0062] In one implementation of this embodiment, the selection of lithium salts is also carefully considered to further enhance the performance of the composite protective film 4. This embodiment selects lithium salts with high ion conductivity and chemical stability, specifically including lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium bisfluorosulfonyl imide (LiFSI) and lithium trifluoromethanesulfonate (LiCF3SO3), which can be used alone or in combination in any proportion.

[0063] Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) is known for its high ionic conductivity and good thermal stability, and can maintain stable ionic conductivity over a wide temperature range. Lithium bis(trifluoromethanesulfonyl)imide (LiFSI) has a lower melting point and higher ionic dissociation, which helps to improve the ionic conductivity of the electrolyte. Lithium trifluoromethanesulfonate (LiCF3SO3) also exhibits good ionic conductivity and chemical stability, and is one of the commonly used lithium salts in solid electrolytes.

[0064] By selecting and combining these high-performance lithium salts, the ion conductivity of the composite protective film 4 can be further optimized, and the charge and discharge efficiency and cycle stability of the battery cell can be improved, thereby ensuring that the solid-state battery cell can exhibit excellent performance under various conditions of use.

[0065] In one implementation of this embodiment, the thickness of the composite protective film 4 is precisely controlled and set to 2 um. The selection of this thickness is the result of in-depth research and optimization, aiming to achieve the best balance between performance and cost.

[0066] On the one hand, the thickness of 2um is enough to provide sufficient mechanical support and chemical stability, protecting the electrode material from the external environment while ensuring efficient conduction of ions in the solid electrolyte. On the other hand, the thinner thickness helps to reduce the amount of materials used, reduce costs, and help improve the energy density of the battery cell.

[0067] In addition, the 2um composite protective film 4 can also form a good interface contact with the electrode material, reduce the interface impedance, and improve the charge and discharge performance and cycle stability of the battery. Therefore, the selection of this thickness not only reflects the ultimate pursuit of battery performance in this embodiment, but also demonstrates the inventor's profound accumulation and innovation ability in the field of materials science.

[0068] In one implementation of this embodiment, the thickness of the diaphragm 3 is further optimized and set to be less than 10 um. This innovative design not only reflects the unremitting pursuit of lightweight and high energy density of the battery in this embodiment, but also demonstrates the inventor's profound accumulation in the fields of material science and battery technology.

[0069] By using a diaphragm 3 with a thickness of less than 10 um, the ineffective space inside the battery can be significantly reduced, and the energy density of the battery cell can be improved. At the same time, a thinner diaphragm helps to shorten the transmission path of ions inside the battery and improve the charging and discharging efficiency of the battery.

[0070] In addition, thanks to the introduction of the composite protective film 4, even if the thickness of the separator 3 is greatly reduced, the mechanical strength and chemical stability of the battery cell can still be fully guaranteed. The composite protective film 4 can not only effectively prevent the electrode material from falling off and short circuiting, but also improve the high temperature resistance and cycle stability of the battery cell.

[0071] In summary, through careful design and optimization, this embodiment successfully achieves a further reduction in the thickness of the diaphragm 3, opening up a new path for improving the performance and reducing the cost of solid-state battery cells.

[0072] Although the terms such as positive electrode sheet, negative electrode sheet, separator, composite protective film, etc. are used more frequently in this application, the possibility of using other terms is not excluded. These terms are used only to more conveniently describe and explain the essence of the present invention; interpreting them as any additional limitation is contrary to the spirit of the present invention.

[0073] A solid-state battery cell provided in an embodiment of the present invention forms a composite protective film including MOF material, solid electrolyte material, adhesive and lithium salt by coating on the surface of the positive electrode plate and the negative electrode plate respectively, so that there is no need to coat the solid electrolyte material on the diaphragm. Therefore, not only can a thinner diaphragm of less than 10 um be used, which is beneficial to reduce weight and improve energy density, but also the process difficulty can be reduced and the battery's dynamic performance and high temperature resistance can be improved.

[0074] Embodiment 2

[0075] Please refer to Figure 2 , is a schematic flow chart of a method for preparing a solid-state battery cell provided in Embodiment 2 of the present invention, and the method is applicable to the scenario of preparing a solid-state battery cell. The method specifically comprises the following steps:

[0076] S101. Mix and dissolve MOF material, solid electrolyte material and binder in a certain proportion, and add lithium salt thereto to obtain a mixed slurry.

[0077] It should be noted that, for example, LATP is selected as the solid electrolyte material and LiCF3SO3 is selected as the lithium salt.

[0078] In an implementation of this embodiment, the step S101 may be further refined to include the following contents:

[0079] Mix and dissolve the MOF material, solid electrolyte material and binder in a certain proportion, and add lithium salt thereto;

[0080] The mixture was stirred at room temperature for 24 hours to obtain a mixed slurry.

[0081] In one implementation of this embodiment, the method further includes the preparation of MOF materials, specifically as follows:

[0082] Zinc nitrate hexahydrate and 2-methylimidazole were stirred and dissolved in methanol in a certain proportion, and then allowed to stand at room temperature for 12 hours, and then the white precursor powder was collected by filtration and washing. After being completely dried at 80°C, the precursor was placed at 500°C for 3 hours in a nitrogen atmosphere, with a heating rate of 3°C / min, to obtain MOF powder.

[0083] S102, uniformly coating the mixed slurry on two opposite surfaces of the positive electrode sheet and the negative electrode sheet respectively by coating technology.

[0084] In one implementation of this embodiment, the method further includes preparing a positive electrode sheet, specifically as follows:

[0085] NCM material, conductive acetylene black and adhesive (such as polyvinylidene fluoride, PVDF) are mixed in a mass ratio of 8:1:1, dispersed in N-methylpyrrolidone (NMP), and then coated on two opposite surfaces of aluminum foil, and dried to obtain the positive electrode sheet.

[0086] S103, drying and curing the coated positive electrode sheet and negative electrode sheet, and rolling them to form composite protective films on the surfaces of the positive electrode sheet and negative electrode sheet respectively.

[0087] It should be noted that this step is to dry and solidify the coated electrode under specific conditions to form a stable solid electrolyte-electrode interface, and the thickness of the protective film is controlled to be 2 um by rolling.

[0088] S104, stacking the positive electrode sheet, the separator and the negative electrode sheet in sequence to form a solid-state battery cell.

[0089] In order to verify the feasibility and effectiveness of the solution provided in this embodiment, this embodiment uses the solid-state battery cell obtained in step S104 as an experimental example for relevant tests, and under the same process, by not preparing a protective film as a comparative example, or, in step S101, no MOF material is added or only the binder PVDF is added to prepare battery cells with protective films of LATP and PVDF as comparative examples, and then relevant tests are also carried out.

[0090] The test results are as follows Figure 3 As shown, Figure 3 The following are the powder removal states of the diaphragm surface of different groups of cells after 85℃ high temperature treatment. Figure 3 It can be seen that the experimental example (MOF+LATP composite protective film) improves the high temperature resistance of the battery and can effectively inhibit the high temperature powder removal phenomenon.

[0091] The beneficial effects of the embodiments of the present invention are:

[0092] (1) MOF materials can be used as auxiliary matrices for solid electrolytes. They have special pores distributed throughout the body and have the characteristics of high specific surface area, providing a fast channel for lithium ion transmission;

[0093] (2) The electrode protection film can effectively reduce the solid-solid interface impedance, improve wettability, reduce the use of electrolyte, and increase energy density;

[0094] (3) Enhanced interface stability and safety, and improved the electrochemical performance of the battery;

[0095] (4) The technology related to electrode coating is mature and the process is simple.

[0096] Embodiment 3

[0097] A third embodiment of the present invention provides a solid-state battery, comprising a cell of the solid-state battery provided in the first embodiment above.

[0098] This innovative design not only inherits all the advantages of the battery cell of Example 1, such as high ionic conductivity, excellent mechanical properties, optimized energy density and outstanding high temperature resistance, but also further improves the overall performance of the solid-state battery by integrating the synergistic effect of various components.

[0099] Specifically, the battery cell of the solid-state battery is composed of a positive electrode sheet, a negative electrode sheet, a separator and a composite protective film, wherein the composite protective film is formed by coating a mixture of MOF materials, solid electrolyte materials, adhesives and lithium salts, which effectively improves the ion conduction efficiency and mechanical strength of the battery cell. At the same time, the thickness of the separator is precisely controlled within the range of less than 10um, further reducing the weight of the battery and improving the energy density.

[0100] In addition, the solid-state battery in Example 3 has also been rigorously tested and verified to ensure that it can perform excellently under various conditions of use. Whether in high temperature, low temperature or conventional environment, the battery can maintain stable charge and discharge efficiency, cycle life and safety performance, providing a reliable power source for electric vehicles, energy storage systems and other fields.

[0101] In summary, the solid-state battery provided in the third embodiment of the present invention, with its excellent performance and innovative design, will become one of the important directions for the development of future battery technology.

[0102] Finally, it should be noted that although the above embodiments have been described in the specification and drawings of this application, this does not limit the scope of patent protection of this application. All technical solutions generated by replacing or modifying equivalent structures or equivalent processes based on the essential concept of this application using the contents recorded in the specification and drawings of this application, as well as directly or indirectly implementing the technical solutions of the above embodiments in other related technical fields, are included in the scope of patent protection of this application.

Claims

1. A solid-state battery cell, characterized in that: It comprises a positive electrode sheet (1), a negative electrode sheet (2), a separator (3) and a composite protective film (4); wherein: The positive electrode sheet (1), the separator (3) and the negative electrode sheet (2) are stacked in sequence; The positive electrode sheet (1) and the negative electrode sheet (2) both comprise a first surface and a second surface which are arranged opposite to each other, wherein the first surface is a surface close to a side of the diaphragm (3); The composite protective film (4) is formed on both the first surface and the second surface by coating; The composite protective film (4) comprises MOF material, solid electrolyte material, adhesive and lithium salt.

2. The solid-state battery cell according to claim 1, characterized in that: The MOF material is UIO-66 or ZIF-8; The MOF material is prepared by a template method or a direct synthesis method.

3. The solid-state battery cell according to claim 1, characterized in that: The solid electrolyte material is any one or a combination of PEO, PAN, LATP, and LLZO.

4. The solid-state battery cell according to claim 1, characterized in that: The lithium salt is any one or a combination of LiTFSI, LiFSI, and LiCF3SO3.

5. The solid-state battery cell according to claim 1, characterized in that: The thickness of the composite protective film (4) is 2 um.

6. The solid-state battery cell according to claim 1, characterized in that: The thickness of the diaphragm (3) is less than 10 um.

7. A method for preparing a solid-state battery cell, for preparing the solid-state battery cell according to any one of claims 1 to 6, characterized in that: The method comprises: The MOF material, the solid electrolyte material and the binder are mixed and dissolved in a certain proportion, and lithium salt is added thereto to obtain a mixed slurry; The mixed slurry is uniformly coated on two opposite surfaces of the positive electrode sheet and the negative electrode sheet respectively by coating technology; Drying and curing the coated positive electrode sheet and negative electrode sheet, and rolling them to form composite protective films on the surfaces of the positive electrode sheet and negative electrode sheet respectively; The positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence to form a solid-state battery cell.

8. The preparation method according to claim 7, characterized in that: The step of mixing and dissolving the MOF material, the solid electrolyte material and the binder in a certain proportion and adding lithium salt thereto to obtain the mixed material comprises: Mix and dissolve the MOF material, solid electrolyte material and binder in a certain proportion, and add lithium salt thereto; The mixture was stirred at room temperature for 24 hours to obtain a mixed slurry.

9. The preparation method according to claim 7, characterized in that: The method further comprises: The NCM material, conductive acetylene black and adhesive are mixed in a mass ratio of 8:1:1, dispersed in NMP, coated on two opposite surfaces of the aluminum foil, and dried to obtain the positive electrode sheet.

10. A solid-state battery, characterized in that: A battery cell comprising a solid-state battery as claimed in any one of claims 1 to 6.